A Modular Architecture and a Cost-Model to Estimate the Overhead of Implementing Confidentiality in Cloud Computing Environments - Storch, Mauro; Meyer, Vinícius; Zorzo, Avelino; De Rose, Cesar A. F. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2024)
Cloud computing has become increasingly popular among organizations. As a result, security has become a major concern in the adoption of cloud computing environments. To ensure confidentiality and prevent data leakage, organizations have adopted various security measures, including sophisticated authentication methods and strong cryptography algorithms. However, implementing these measures generates additional overhead that could impact resource consumption and performance at user level. This paper proposes a modular architecture for a full-stack confidentiality cloud and a model to estimate implementation costs for each component that can be used as a blueprint to implement the needed confidentiality in a particular cloud scenario and estimate the resulting overhead. It contributes to the literature by enabling cloud administrators and users to leverage confidentiality based on their security needs and budget. Preliminary experiments show that our cost model achieves a high level of accuracy, up to 95%.